A Review on the Hypotheses about Arterial Hypertension from the Viewpoint of Traditional Persian Medicine: - Hasani, Davoud; Bahrami, Mohsen; Kamalinejad, Mohammad; Ahanghar, Hassan; Faghihzadeh, Soghrat; Dadmehr, Majid (Galen Medical Journal, 2020)
Hypertension is one of the most common chronic diseases in recent decades worldwide. It has been distinguished as the main risk factor of coronary artery disease, aortic dissection, heart failure, renal failure, cerebrovascular diseases, and death. In recent years, the global attention has been paid to complementary medicine to preventive, diagnostic and treatment strategies for hypertension, in previous studies, the history of hypertension from the viewpoint of traditional Persian medicine have been reviewed and several hypotheses raised. In this article, we present the concept of an Iranian physician namely Ali ibn Sahl Rabban al-Tabari on hypertension, which has not been considered properly until now. He defined a state called â€œHayajan al-damâ€ that has clinical manifestations similar to hypertension, although these are not the same, also, we reviewed the viewpoint of other Persian medicine scholars namely Rhazes, Haly Abbas, Akhawayni and Avicenna for this topic. [GMJ.2020;9:e1065]